Allergic Reaction due to Anti-Tuberculosis Drugs, How to Manage? - Nur Prasetyo Nugroho; Tutik Kusmiati (Faculty of Medicine Universitas Airlangga, 2021)
Tuberculosis (TB) still becomes a significant health problem in Indonesia. The first-line anti-tuberculosis drug (ATD) is still the most effective TB drug, but it can have some side effects. One of them is allergic skin reactions that can affect a patient's compliance. Allergic reactions due to ATD are found in 4-6% of TB cases and are the third most frequent side effect after gastrointestinal and liver function disorder. All first-line ATD can cause allergic reactions. Allergic reactions due to ATD can be mild, such as itching and reddish rashes, to severe and life-threatening rashes, such as anaphylactic shock, Steven Johnson Syndrome (SJS), and Toxic Epidermal Necrotic (TEN). The most important things in the management are identifying and stopping drugs. It includes drug challenge and desensitization of causing drug. Desensitization must be distinguished from drug challenge or provocation tests, which are diagnostic tools. The proper management of ATD allergic reactions can improve compliance and patient's outcomes.